PERBANDINGAN HASIL BELAJAR IPS MENGGUNAKAN MODEL TIPE NHT DAN MM - Jenni Ayuningtyas; Yon Rizal; Nurdin Nurdin (FKIP Unila, 2014)
This study have a purpose to know :1) the differences average of learning outcomes using the Integrated Social learning models of NHT with MM. 2) whether the increasing of IPS Integrated learning outcomes of students who use the learning model NHT type is higher than the MM type. This study used an experimental method with a comparative approach. The results showed : a) there is a difference in average learning outcomes using the Integrated Social learning models of NHT with MM. Based on the analysis of data obtained significant 2.48 2,01. b) improvement of learning outcomes of students who use the Integrated Social learning models of type NHT higher than the MM type. Based on the comparison of the average of each items on the experimental class and the control is 0,60 0,51. Penelitian ini bertujuan untuk mengetahui: 1) perbedaan rata-rata hasil belajar IPS Terpadu menggunakan model pembelajaran tipe NHT dengan tipe MM. 2) apakah peningkatan hasil belajar IPS Terpadu siswa yang menggunakan model pembelajaran tipe NHT lebih tinggi dibandingkan dengan tipe MM. Penelitian ini menggunakan metode eksperimen dengan pendekatan komparatif. Hasil penelitian menunjukkan; a) terdapat perbedaan rata-rata hasil belajar IPS Terpadu menggunakan model pembelajaran tipe NHT dengan tipe MM. Berdasarkan analisis data diperoleh signifikan 2,48 2,01. b) peningkatan hasil belajar IPS Terpadu siswa yang menggunakan model pembelajaran tipe NHT lebih tinggi dibandingkan dengan tipe MM. Berdasarkan perbandingan rata-rata hasil belajar pada kelas eksperimen dan kontrol yaitu 0,60 0,51. Kata kunci: hasil belajar, mm, nht.